Competency improvement through internship: An evaluation of corporate social responsibility program in vocational school - Mgs. Ahmad Ramadhani; Ety Rahayu (Institute of Advanced Engineering and Science, 2020)
The high unemployment rate in Indonesia derived from vocational school graduates could be alleviated through internship as a part of Corporate Social Responsibility program that deployed by company together with school to equip its students or graduates with set of competences, therefore they will be competent and able to compete in job market, especially in the era of disruptive technologies. This applied research of evaluation using qualitative approach aimed to evaluate the input and process of the corporate social responsibility program in vocational internship conducted by an oil and gas manufacturing company in Indonesia. The results of this revealed some inputs that were the source of program success and processes that determined the quality of the program. Aspects of input generally met the ideal criteria such as competent program staff, participant characteristic reflecting program objectives, flexible and synchronized curriculum, adequate facility, and available procedure. Aspects of the process complied with regulations and procedures as well. Both aspects resulted the achievement of outcome that exceeded expectation such as competence improvement, cost saving, awards and provide information to be replicated by other institutions.